Utilization of Cabbage as an Artificial Feed Material for Pearl Catfish (Clarias gariepinus) Fry Growth - Komsanah Sukarti; Henny Pagoray; Andi Nikhlani (Jurnal Perikanan dan Kelautan, 2022)
Pearl catfish has the main advantage of fast growth. To maximize this growth, one of the things that must be considered is the feed given. The use of factory feed for catfish seeds is common, so it is necessary to use feed raw materials that are around to be used as raw materials for homemade feed. Vegetable waste such as cabbage and tofu dregs can be used as fish feed which is processed into pellets. Cabbage vegetable waste, tofu dregs, bamboo shoots and bran have protein and carbohydrates that can be used for fish growth. This study consisted of 2 stages, namely stage 1 analyzing the comparison between factory feed and homemade feed and stage 2 analyzing the difference in dosage of homemade feed on the growth and efficiency of pearl catfish (C. gariepinus) seed feed. Data were analyzed using 2 independent samples (unpaired) t-test and ANOVA test. The results showed that the provision of factory feed and homemade feed did not have a significant effect on the growth of length, weight, and feed efficiency of catfish fry. Catfish seeds can be fed homemade feed with ingredients from fermented cabbage waste, tofu dregs flour, rebon flour, bran flour, plus vitamins and minerals. The results of the analysis of variance in the treatment of different feed doses (4%, 5%, 6%, 7%, and 10% per fish body weight), had a significant effect on the growth of catfish length and weight, and had no significant effect on feed efficiency. The higher the dose given for the maintenance period of 30 days of catfish fry gave a good effect with the best dose of 10% per fish body weight.